Remote learning during COVID-19 and transformative learning theory: Tendency towards Quadruple Helix model for future post-secondary education in Indigenous contexts - Amzad Hossain; Ying Kong; Amjad Malik (Journal of Innovation and Entrepreneurship, 2023)
This paper aims to examine UCN (University College of the North) students' remote learning experience during the COVID-19 pandemic to provide a reference for future remote education in Indigenous contexts. Survey data are used for empirical analysis of the five themes: socio-demographic contexts; social activities, stress, and well-being; academic performance; course delivery; and student support services. Transformative learning theory and Quadruple Helix Model are used as a framework to explore the breadth and depth of such five themes. As the descriptive study shows, the majority of UCN students are over 25 years old and study in their first and second year with major challenges such as Internet connectivity, private space, and interruption. Mean values reveal that the remote learning performance is determined by concerns about COVID-19 infection, mental and physical health, isolation and lack of socio-cultural activities, students' self-preparedness and motivation, and support services. The regression analysis shows that students' concerns about COVID-19 infection interference with course completion are directly affected by their worries about themselves or someone in their families who could be exposed to COVID-19, their mental health, and blended course delivery. Therefore, students' remote learning performance and their well-being will be enhanced if we take into consideration improving social distancing, educational technology, and course delivery with community-university culturally responsive collaboration. The research findings and the reviewed literature attest that transformative learning theory fits UCN's remote learning practices to meet educational goals through the university-community collaboration, which is supported by the Quadruple Helix model. As a result, such remote learning practices engage students, particularly Indigenous students, and the practices will help upgrade universities with similar attributes globally into Mode 3 universities, contributing to community economic development.
Keywords: 650; Indigenous students; Mode 3 university; Quadruple Helix model; Transformative learning theory; UCN remote learning practice; University-community collaboration